Profiling and investigating the determinants of strength of brand preference of beer-drinking undergraduates in Singapore. - Goh, Julynn Kailin. (2013)
With the potential growth in the Singapore beer market, marketing managers are utilizing various forms of marketing strategies to appeal to the younger crowd. This study sets out to reconcile prior literatures that seemingly contradict each other in trying to establish the effectiveness of marketing strategies in developing strong brand preference. Trends in the Singapore market, such as the growth in the youth segment and the phenomenon of brand switching, pose a great challenge to managers in making the best decisions for their marketing strategies.